Perbandingan Algoritma Raita Dan Apostolico Crochemore Untuk Pencarian Data Perpustakaan Menggunakan Metode Eksponensial - Herman Krismon Simbolon (Graha Mitra Edukasi, 2023)
The Raita and Apostolico Crochemore algorithms are string matching algorithms that can be used to simplify the search process for a search engine. The two algorithms have different search characteristics to find string matching results. Algorithms that have more optimal speed in string matching will certainly be more useful. In this study, the authors compare the two algorithms using the Exponential Method so that it is easy to find out which method is more optimal in searching between the two algorithms. A case study in string matching is used to compare the two methods, namely in the process of searching for library data that the author will build using Visual Basic Net 2008.